Desenvolvimento de barra alimentícia adicionada de café: estudo de marketing - Sousa, Maísa Mancini Matioli de (2016)
The consumption of snack bars is based especially on the demand for practical and nutritious food. Coffee is highlighted for being appreciated and consumed worldwide, presenting elevated antioxidant activity, in addition to peculiar sensorial attributes. Therefore, it has great potential for use in many formulations. However, the success in the acceptance of a new product also derives from adequate marketing strategies. In this context, the present study aimed at evaluating the feasibility of introducing to the market a snack bar added with coffee, by means of sensorial acceptance and purchase intent of the consumers, in addition to identifying the best concept and the possible market segments. This work was a qualitative, by means of a focus group (content analysis), and quantitative research, by means of sensorial analysis and structures questionnaires (descriptive – frequency distribution, arithmetic mean, crosstabs and t test – and multivariate – cluster and discriminate analysis - statistical techniques). With the results, we showed that the main aspects considered by the consumers regarding the snack bar added with coffee. According to the qualitative evaluation, the consumer prefers packaging with matte colors ranging in the tones related to the coffee grain. The analysis of the quantitative data allows us to infer that the evaluations of the product regarding overall impression, purchase intent, preference and expectation before and after consuming the product are better for packaging containing the information “special coffee flavor – 100% arabic”. Regarding market segment, it was possible to conclude that, of the three extracted groups, the group of “healthy and conscious consumers” was the segment with higher potential for exploitation regarding purchase and consumption of the snack bar added with coffee.